Peran Ibnu Sina dalam Sejarah Filsafat Islam dan Sains Modern - Salsa Bila Ivanda; Nur Annisa; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the intellectual contributions of Ibn Sina (980–1037 AD) to the development of Islamic philosophy and modern science. As a prominent polymath, Ibn Sina successfully combined Aristotelian and Neoplatonic ideas with Islamic theology, thereby forming a systematic philosophical framework that influenced both the Islamic world and medieval Europe. The main objectives of this study are to analyze Ibn Sina's role in the history of Islamic philosophy, his contributions to the advancement of science, and the relevance of his thoughts in the contemporary era. This study uses a qualitative method with a literature review approach, focusing on primary and secondary sources related to Ibn Sina's works and their historical impact. The results of this study show that Ibn Sina's works, particularly Al-Qanun fi al-Tibb and Al-Syifa, have not only been the main references in the fields of medicine and philosophy for centuries, but also laid the foundation for the development of modern science. The implication of this research is that Ibn Sina's intellectual legacy remains relevant in today's academic discourse, emphasizing the importance of integrating philosophy, science, and religion in building human civilization.